-(a+3)=-2(2x+3)-7

Simple and best practice solution for -(a+3)=-2(2x+3)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(a+3)=-2(2x+3)-7 equation:


Simplifying
-1(a + 3) = -2(2x + 3) + -7

Reorder the terms:
-1(3 + a) = -2(2x + 3) + -7
(3 * -1 + a * -1) = -2(2x + 3) + -7
(-3 + -1a) = -2(2x + 3) + -7

Reorder the terms:
-3 + -1a = -2(3 + 2x) + -7
-3 + -1a = (3 * -2 + 2x * -2) + -7
-3 + -1a = (-6 + -4x) + -7

Reorder the terms:
-3 + -1a = -6 + -7 + -4x

Combine like terms: -6 + -7 = -13
-3 + -1a = -13 + -4x

Solving
-3 + -1a = -13 + -4x

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -1a = -13 + 3 + -4x

Combine like terms: -3 + 3 = 0
0 + -1a = -13 + 3 + -4x
-1a = -13 + 3 + -4x

Combine like terms: -13 + 3 = -10
-1a = -10 + -4x

Divide each side by '-1'.
a = 10 + 4x

Simplifying
a = 10 + 4x

See similar equations:

| 2(t+2)=14 | | 81xsquared+8=0 | | f=-1 | | 41(x-6)+4=6x-8 | | 9x+7(3x-4)=7-5x | | 4x-2(x-3)=-5+4x+1 | | 9v-9=3(v-5) | | 2x^2+x^2=25*25 | | 4-2(x-3)=5+4x+1 | | 4x-15=x+51 | | 0.5x+9= | | 208=-13 | | 12x^3+28x^2+13x-45=0 | | 3x+10=7x-5 | | 25x^4-50x^3+25x^2=0 | | 8y+2=4x | | 3x+20=41 | | X+(-3)+9=-1+14 | | h(t)=-4.9t^2+24t+8 | | 4x^7-32x^5= | | 34+20=41 | | 2x-38=180 | | x^2+24-11x= | | 27=7+4w | | e^10x+6=12 | | 9a+27= | | 17=-5m+3 | | 5(y+4)=8y-45 | | 4x+7x-38=76-8x | | 3a+2w-5a-9w= | | 7+24m=28+17m | | 8x-3y=37 |

Equations solver categories